Creación de un recurso didáctico lúdico digital, en la materia de ciencias naturales del quinto año para apoyar al proceso de enseñanza aprendizaje en la escuela de educación básica Ciudad de Loja, periodo 2016-2017 - Armijos Merino, Leonardo Antonio (2018)
The present research work was based on the construction of a recreational and digital didactic resource based on theories and new educational approaches that can be implemented within the classroom in order to adapt to the technological evolution presented by the children of the city of Loja. This was socialized in the fifth parallel year "C" of the School of Basic Education "City of Loja", where the experiences, surveys and examinations that children have problems in the teachinglearning process in the field of science are detected natural, with the themes of soil and minerals, which is in Unit 5 of the book provided by the Ministry of Education. The research work tried to solve the problems raised in order to achieve a better performance and streamline the educational activity of children. For the development of the ludic and digital didactic resource, the dynamic methodology, which ensures that the pedagogical part is present in all the elaboration. The resource includes learning and evaluation activities, aimed at supporting the academic work of the teacher and the students.